VanZ Reduces the Binding of Lipoglycopeptide Antibiotics to Staphylococcus aureus and Streptococcus pneumoniae Cells - Vimberg, Vladimir; Zieglerová, Leona; Buriánková, Karolína; Branny, Pavel; Balíková Novotná, Gabriela (Frontiers in Microbiology, 2020)
The vanZ, a member of the VanA glycopeptide resistance gene cluster, confers resistance to lipoglycopeptide antibiotics independently on cell wall precursor modification by vanHAX genes. Orthologues of vanZ are present in the genomes of many clinically relevant bacteria, including Enterococcus faecium and Streptococcus pneumoniae; however, they are missing in Staphylococcus aureus. Here we show that expression of enterococcal vanZ paralogues in S. aureus increases minimal inhibitory concentrations of clinically used and experimental lipoglycopeptide antibiotics. Reduction of binding of fluorescently labeled lipoglycopeptide antibiotic to the cells suggests the mechanism of VanZ-mediated resistance. Besides, using genomic vanZ gene knockout mutant of Streptococcus pneumoniae, we have shown that the ability to compromise the activity of the lipoglycopeptide antibiotics by reducing its binding is a more general feature of VanZ-superfamily proteins.